A Miniaturized Ultra-Wideband Radar for UAV Remote Sensing Applications - Abushakra, Feras; Jeong, Nathan; Elluru, Deepak N.; Awasthi, Abhishek K.; Kolpuke, Shriniwas; Luong, Tuan; Reyhanigalangashi, Omid; Taylor, Drew; Gogineni, S. Prasad (IEEE microwave and wireless components letters, 2022)
This letter presents a novel approach to build a compact lightweight unmanned aerial vehicle (UAV) radar for remote sensing applications. The proposed radar exploits the recent advancement of an automotive radar chip for broadband chirp generation and rapid data processing. To compensate for the path losses and improve penetration at the millimeter-wave (mm-wave) frequency range, up- and down-converters are developed to generate an ultra-wideband (UWB) (3.25-5.15 GHz) chirp signal. The total payload of the radar is 2.5 kg. The proposed radar is installed on an UAV and tested in the field at a 100-m altitude above the ground surface. The results show that the compact low-power UWB radar can be used to map vegetation and soil moisture with fine resolution.